Occurrence of paralytic scoliosis in patients with poliomyelitis reporting at Fauji Foundation Hospital, Rawalpindi - Muhammad Osama; Naureen Tassadaq (Journal of the Pakistan Medical Association, 2020)
Abstract Pakistan is one of the only three countries in the world with an enduring poliovirus transmission, making poliomyelitis an important health concern for Pakistan. Paralytic scoliosis is a common musculoskeletal dysfunction associated with poliomyelitis. To determine the occurrence of paralytic scoliosis a cross-sectional study was conducted at Fauji Foundation Hospital, Rawalpindi from 2015 to 2018. All patients with poliomyelitis reporting to the hospital were included, whereas patients with scoliosis but no poliomyelitis were excluded. Cobb’s angle was used to determine the severity of scoliotic curves. Pearson correlation was used to determine the correlation of Cobb’s angle with age and Independent T-test was used to determine the difference in terms of gender. Confidence interval was kept at 95%. A total of 51 patients with poliomyelitis were included in the study with a mean age of 28.58±15.07 years.